Spatial analysis of gas stations in Bani Walid city Using GIS (Journal of Libya for geographical studies, 2024)
All science has witnessed a great development and difference in style Scientific research and it is now necessary to search for Faster scientific reach, easier and less expensive, than Helps to provide a clearer and more accurate scientific idea, in the light of which current research has benefited from GIS 'ability to study the image Distribution of gas stations in Bani Walid City The extent to which it is influenced by geographical factors or their repercussions on the distribution and level of the service, and the disclosure of what spatial relationships it governs with discrepancies spatial and general pattern of geographical distribution.We have based this research on the descriptive and analytical approach through the use of spatial statistical analysis tools in Arc Map 10.8 To measure the balance in gas station distribution through Measures of centralism and analysis of the closest neighbor, The results of the analysis showed that the value of the neighbourhood link that had been made Applied to the city's gas stations, amounting to 1.12 Thus, the pattern of distribution of these stations is scattered, and the results have shown the validity of the hypothesis that the distribution of fuel stations is incompatible with the distribution of population density, and many have been presented Results in the form of digital maps explain the nature of the spatial model of distribution.
Keywords: distribution pattern; service range; population density; standard distance